Pengembangan Kawasan Wisata Berbasis Partisipasi Masyarakat Lokal di Koripan 1 Dlingo - Wulaningrum, Puspita Dewi (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2018)
Koripan 1 in Dlingo has tourism potential that can be developed to improve people’s economy, there is water springs from sendang Umbul Ndeso and petilasan Gunung Pasar. In addition, because the majority of people’s livelihood are farmers, the results of agricultural processing can also be used as a means of supporting the tourist area. This activity aims to develop the potential tourist area in Koripan 1 which is expected to be an alternative income residents so that the economy increases. The method used is the analysis of village-based tourism development process based on local community participation then reduced to the steps of village development. The results and implications of this activity include the design of tourism objects Umbul Ndeso and petilasan Gunung Pasar, development of early stage of the form of gazebo, street lighting and road directions, training for the community related to improving the quality of farm produce and licensing P-IRT, and marketing through online media. The conclusion of this activity is the development program of tourist area of Koripan 1 has assisted in building the tourist village as well as providing direction for sustainable development step for the community. This activity has also provided education for the citizens about the importance of quality and licensing for food processing business of agricultural products. Keywords: Tourism, Local Community Participation, Processed Agricultural Products